Effects of tunnel fires on the mechanical behaviour of rocks in the vicinity – A review. (February 2021) - Wasantha, P.L.P.; Guerrieri, Maurice; Xu, Tao
Highlights: Heat can be transferred to surrounding rock during tunnel fires. Rock mechanical behaviour under fire is poorly understood. New testing arrangement is proposed to study the rock behaviour under tunnel fire. Effects of various factors on rock behaviour under tunnel fire are discussed. Abstract: The number of underground tunnels used for transportation has markedly increased globally during the past decade. This has resulted in an increased number of tunnel fire incidents, prompting designers to analyse the effects of tunnel fires on the tunnel and the near vicinity in greater detail. This is of particular importance for tunnels constructed in urban areas where above- and below-ground structures can be highly sensitive to surrounding ground deformations and groundwater level fluctuations. Tunnels may have unprotected unlined sections and/or protected lined sections, and those constructed using tunnel boring machines (TBMs) usually have a thick segmented lining structure. While rock is directly exposed to extreme heat during tunnel fires in unlined tunnel sections, some heat can still cross the lining structure into the substrate, especially when concrete spalling (dislodgement of heated concrete pieces) occurs in extreme fires, in tunnels with concrete lining structures. Longer fire durations and the presence of internal reinforcements (anchors/bolts) further support this heat transfer. In this paper, previous studies on the effects of tunnel fires on the behaviour of both concrete and different rocks under elevated temperatures are critically reviewed. While numerous previous studies have investigated the effects of tunnel fires on concrete/shotcrete lining structures, very few studies have focused on the effects of tunnel fires on the surrounding rock mass. The vast majority of studies of the behaviour of various rocks at high temperatures have used low and constant heating rates, which do not resemble the temperature–time variation of any established tunnel fire curve. The potential temperature rise within the rock due to tunnel fires is still not well understood and a novel testing arrangement is proposed here to explore this. This testing set-up also enables the evaluation of the role of rock anchors/bolts on heat transfer into rock and the effect of fire on their reinforcing capacity. In addition, it allows a more realistic assessment of the spalling behaviour of concrete lining panels. A particular effort is made to understand the thermo-mechanical behaviour of various rocks under real fire conditions through meaningful correlations with corresponding behaviours of concrete which are relatively well documented. Furthermore, some additional challenges when assessing the thermo-mechanical behaviour of rocks in fire situations compared with concrete are discussed. These include the presence of macro-scale discontinuities, scale effects and transformation plasticity. Overall, this review contributes to a better understanding of the thermo-mechanical behaviour of rocks in tunnel fires, proposes new directions for future research, and contributes to safe, economical and sustainable tunnel designs in future.